2003
DOI: 10.1194/jlr.m300123-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of carnitine palmitoyltransferase in the rat small intestine reduces export of triacylglycerol into the lymph

Abstract: Following digestion of dietary triacylglycerol (TAG), intestinal epithelial cells absorb fatty acids and monoacylglycerols that are resynthesized into TAG by enzymes located on the endoplasmic reticulum (ER).The intestinal epithelial absorptive cell has little control over the rate of entry of the absorbed products of lipid digestion, fatty acids (FAs) and monoacylglycerols (MAGs). These must be disposed of rapidly, otherwise the cells risk destruction of their cellular membranes. The enterocytes are able to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…the roles of CPT1a and CPT1b, is to increase the capacity of fatty acid flux into the mitochondria and to improve insulin sensitivity and glucose utilization by eliminating unoxidized fatty acids (Bruce et al 2009 ;Folmes & Lopaschuk, 2007). Although the role of CPT1c is far from fully elucidated, it has been suggested that CPT1c might alter the synthesis of ceramide and sphingolipids in neurons through facilitating the entry of palmitoyl CoA to the ER lumen (Sierra et al 2008 ;Washington et al 2003). The synthesis of ceramide and sphingolipids affects the lipid composition of the cell membrane, changing the environment and the activity of the membrane receptors (Chattopadhyay & Paila, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…the roles of CPT1a and CPT1b, is to increase the capacity of fatty acid flux into the mitochondria and to improve insulin sensitivity and glucose utilization by eliminating unoxidized fatty acids (Bruce et al 2009 ;Folmes & Lopaschuk, 2007). Although the role of CPT1c is far from fully elucidated, it has been suggested that CPT1c might alter the synthesis of ceramide and sphingolipids in neurons through facilitating the entry of palmitoyl CoA to the ER lumen (Sierra et al 2008 ;Washington et al 2003). The synthesis of ceramide and sphingolipids affects the lipid composition of the cell membrane, changing the environment and the activity of the membrane receptors (Chattopadhyay & Paila, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…A carnitine acyltransferase system capable of transporting fatty acids from the cytosol across membranes via a fatty acylcarnitine intermediate has been identified at the ER (41)(42)(43). Carnitine acyltransferase enzymes have previously been demonstrated to have a role in TG synthesis in the ER lumen both in vivo in rat small intestine and with a cell-free system, providing evidence for a mechanism that could deliver fatty acid substrates across the ER membrane from the cytosol to the active site of DGAT1 in the ER lumen (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…A working hypothesis is that following an oral fat load, CD36-rich membrane vesicles help shuttle FAs to ER enzymes required for TAG synthesis (Figure 8). For example Dgat1 (28) has been postulated to localize on the luminal side of the ER (29), and FA delivery to Dgat1 and other esterification enzymes could become limiting.…”
Section: Figurementioning
confidence: 99%